NON-PHARMACOLOGICAL MODALITIES FOR TREATING CERVICOGENIC HEADACHE: A SYSTEMATIC REVIEW - RAMESH CHANDRA PATRA; LOBSANG CHONZOM; ARSHDEEP KAUR; ISHIKA (Asian Journal of Pharmaceutical and Clinical Research, 2025)
Objectives: This study aimed to investigate the outcomes of the non-pharmacological modalities in adult patients with cervicogenic headaches. Methods: The systematic review, guided by the PRISMA approach, investigated 29 randomized controlled trials/randomized studies, published from 1997 to 2022, concerning the efficacy of non-pharmacological interventions for cervicogenic headache. The primary endpoints were headache duration, frequency, and intensity; however, the secondary endpoints included several clinical complications of cervicogenic headache. Results: The findings from this study revealed a 97.5–100% satisfaction level in patients who underwent physiotherapy sessions for their cervicogenic headaches. The pooled outcomes revealed noticeable improvements in the range of motion of the cervical spine following the administration of manual therapy, apophyseal glide, trigger point-directed dry/superficial needling, spine mobilization, massage, and Graston procedure. In addition, dry needling, multimodal therapy, spinal manipulative therapy, routine physiotherapy, and other non-pharmacological approaches were found to be effective in improving the disability-level perception of patients with cervicogenic headaches. While the evidence negated the impact of non-pharmacological approaches on psychological distress and cognitive/social functioning, their positive influence on quality of life, pain perception, pressure pain thresholds, performance of neck muscles, and muscle fatigue was emphasized by most of the included studies. Conclusion: This study emphasized the cervicogenic headache management potential of non-pharmacological modalities, including dry needling and cervical spine manipulation procedures; future studies should compare our results with pharmacological modalities to transform the treatment landscape for patients with cervicogenic headaches.